DOS Art and Archeology of Pompeii: Presentation Of The Dossier - Costa Grillo, José Geraldo; A. Funari, Pedro Paulo (Imagem: Revista de História da Arte, 2024)
The result of epistemological changes, which have occurred in the last two decades, in the History of Art, Art and Archeology is the study of the arts of Classical Antiquity considering questions of form, function and context of each artistic work, with the objectives of understanding the purpose and use of buildings and objects, and how these operate within their time and place; how they were intended to be perceived; what messages they convey, and how the physical, historical, economic, political, social and cultural environment shape their meanings for observers.